Approaches to the Selection of the Source Base of the Research of Social-Pedagogical Bases of Development of the Rural School in Ukraine (the Second Half of 1950-s – 1990-s) - Ivanyuk, Halyna (Pedagogical Discourse, 2013)
Basic approaches and principles in the selection of historiography of the research on the topic «Socio-pedagogical principles for the development of rural schools in Ukraine (the second half of 1950-s – 1990-s)» are revealed in the article. The current approaches to the analysis and selection of historiography of historic-pedagogical researches are analyzed. The essential features of research of social-pedagogical bases of the development of rural schools, and their diversity are singled out, that determines the necessity to improve interdisciplinary approach to the selection of sources. The author moves away from the formation approach to the selection of source base of the study. They are classified and presented according to separate groups: historiographical sources, documentary sources, narrative sources and sources of personal origin, mass sources, textbooks sources and electronic sources.